Interprofessional collaboration with child welfare services in the follow up of child neglect at health centres: A qualitative study of public health nurses’ experiences - Bøe, Sølvi; Bondas, Terese (Nordisk Tidsskrift for Helseforskning, 2024)
The public health nurse is in a unique position to detect and help children who are exposed to neglect. In case of neglect, the public health nurses need to enact interprofessional collaboration. In this study, the purpose was to explore and describe public health nurses interprofessional collaboration experiences with child welfare services, when following up child neglect at a health centre. The theoretical perspective was Vik’s typology of different types of collaboration. A qualitative design was chosen, using Braun and Clarke’s reflexive thematic analysis as method and data collection with focus groups and vignette, including 16 public health nurses. The analysis resulted in 4 themes: 1) Addressing parents is a starting point for cooperation with child welfare, 2) Frustration when cooperation with child welfare could be better, 3) Collegial cooperation to help the family and 4) Relationship-building between the professions.